24.3: Short‐Channel Indium‐Gallium‐Zinc Oxide Thin‐Film Transistor Enabled by Thermal Dehydrogenation and Oxidizing Defect‐Suppression. (28th November 2018) - Lu, Lei; Li, Jiapeng; Lv, Nannan; Xia, Zhihe; Feng, Zhuoqun; Wang, Sisi; Wong, Man; Kwok, Hoi Sing
Abstract : The effective "short‐channel effect (SCE)" hindered the downscaling of IGZO TFT and thus prevented its further application to next‐generation displays with much higher resolution and ppi. The "SCE" was found to be caused by the common hydrogen dopant and native donor defect. Although the dehydrogenation can be realized using a heat‐treatment, its efficiency dramatically decreased with the annealing time increasing. On the other hand, improper annealing ambience would rather than reduce but enhance the SCE by generating additional donor defects. The high‐performance short‐channel IGZO TFT was achieved by using a long‐enough thermal oxidization to suppress both hydrogen and defects.